DARI PURITANISME KE KOSMOPOLITANISME: TRANSFORMASI PEMIKIRAN DAN GERAKAN MUHAMMADIYAH DALAM PERSPEKTIF ISLAM BERKEMAJUAN - Asmar Habibi; Muhammad Fauzan; Riko Pilihantoni; Ahmad Lahmi; Mursal Mursal (Ensiklopedia of Journal, 2026)
This article examines the intellectual and organizational transformation of Muhammadiyah from Islamic puritanism toward Islamic cosmopolitanism within the framework of contemporary Islamic thought in Indonesia. Historically, Muhammadiyah emerged as a reformist movement (tajdid) emphasizing the purification of Islamic beliefs and practices through strict adherence to the Qur’an and Sunnah. However, in recent decades, Muhammadiyah has increasingly articulated a cosmopolitan orientation characterized by openness to religious and cultural pluralism, interfaith dialogue, and active engagement in global humanitarian issues. This study employs a descriptive-analytical literature review method, drawing on classical and contemporary scholarly works on Muhammadiyah, Islamic reformism, and Islamic cosmopolitanism. The findings indicate that the shift from puritanism to cosmopolitanism is driven by internal intellectual dynamics, the expansion of modern education and scientific discourse, as well as external factors such as globalization, democratic transformation, and societal pluralism. Empirical examples from the literature demonstrate how the concept of Islam Berkemajuan has been institutionalized through Muhammadiyah’s involvement in education, healthcare, disaster relief, and interfaith cooperation at national and international levels. This transformation does not signify the abandonment of purificatory principles but rather reflects a reorientation of Islamic reform toward inclusivity, ethical universalism, and civilizational engagement. The study concludes that Muhammadiyah’s evolving synthesis of puritanism and cosmopolitanism represents a distinctive model of progressive Islam capable of contributing to both national cohesion and global humanitarian discourse.Keywords: Muhammadiyah, Islamic puritanism, Islamic cosmopolitanism, Progressive Islam, Islam Berkemajuan